2023
DOI: 10.21037/hbsn-21-196
|View full text |Cite
|
Sign up to set email alerts
|

Living donor liver transplantation for Barcelona clinic liver cancer (BCLC) intermediate-stage hepatocellular carcinoma

Abstract: Background: Barcelona clinic liver cancer (BCLC) stage B (intermediate stage) hepatocellular carcinoma (HCC) is highly heterogeneous; thus, identifying the most effective treatment for individual patients represents a significant clinical challenge. However, transarterial chemoembolization (TACE) is the only recommended treatment option. Therefore, we aimed to investigate the patient characteristics and outcomes of living donor liver transplantation (LDLT) for BCLC stage B HCC.Methods: A total of 516 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Additionally, LT represents a valuable surgical option for selected patients with intermediate-stage HCC, as shown in several studies reporting favorable outcomes in terms of survival and recurrency rates. 46 Tsai et al 47 observed a longer OS in BCLC-B patients treated with living donor LT compared with BCLC-B patients not allocated to LT. They delineated how a combination of age, neutrophil to lymphocyte ratio and locoregional treatments before LT were able to stratify the risk of HCC recurrence and mortality in LT patients.…”
Section: Different Available Treatment Options For Intermediate-stage...mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, LT represents a valuable surgical option for selected patients with intermediate-stage HCC, as shown in several studies reporting favorable outcomes in terms of survival and recurrency rates. 46 Tsai et al 47 observed a longer OS in BCLC-B patients treated with living donor LT compared with BCLC-B patients not allocated to LT. They delineated how a combination of age, neutrophil to lymphocyte ratio and locoregional treatments before LT were able to stratify the risk of HCC recurrence and mortality in LT patients.…”
Section: Different Available Treatment Options For Intermediate-stage...mentioning
confidence: 99%
“…However, their data resulted from a retrospective analysis, and LT patients were compared with a population subjected to heterogeneous treatments, including both curative treatments, like radiofrequency ablation (RFA), and palliative treatments, like TACE and systemic therapies. 47 …”
Section: Different Available Treatment Options For Intermediate-stage...mentioning
confidence: 99%
See 1 more Smart Citation